Primary undifferentiated pleomorphic sarcoma of the thyroid: A case report and review of the literature. Issue 7 (February 2018) - Chen, Qiang; Huang, Qing; Yan, Jia-xin; Li, Chao; Lang, Jin-yi
Abstract: Rationale: Primary undifferentiated pleomorphic sarcoma is extremely rare in the thyroid, and can be easily misdiagnosed as anaplastic thyroid cancer. Patient concerns: We present a case of a 71-year-old woman who presented with a rapidly growing painless mass in the neck. Diagnoses–interventions–outcomes: Computed tomography showed a large hypointense mass with hyperdense areas involving whole of the right lobe of thyroid gland and fine-needle aspiration cytology found a few atypical cells. Surgical exploration was performed subsequently and frozen section showed malignant tumor. Therefore, a total thyroidectomy, central, and bilateral lateral neck dissection were performed and adjuvant radiotherapy of 60 Gy was administered. The patient was alive and had no recurrence at 6-month follow-up. Lessons: Although primary undifferentiated pleomorphic sarcoma in the thyroid is extremely rare, patients who presented with a rapidly growing painless mass in the neck should be considered and it is essential to excise the tumor completely as soon as possible.